(untitled) (African Journal of Biomedical Research, 2023)
Universal Health Coverage and the 2030 Sustainable Development Goals have impacted global substance/drug reform policy through strict prohibition and criminalization in the 21st century. Thus, the Covid-19 lockdown and measures have raised concerns regarding the disproportionate impact on persons with substance use, abuse and addiction in South Africa. This paper was guided by Social Learning Theory of substance use and abuse, explaining how interactions with others may contribute to substance use as people learn messages about substance abuse. This has placed more emphasis on the role social structure plays as opposed to individual or psychological factors. This paper takes a broad look at the implication of substance use, abuse and addiction among users amidst the Covid-19 pandemic in South Africa. The study used systematic review derived from articles that were sourced from research databases (such as Scopus, Medline, Sage, Google Scholar etc.), and a total of 84 articles were selected in line with the objectives. Also, a desktop review of key information was adopted in line with the objectives, as there are no definitive data on the extent of substance/drug use in South Africa. The provision of health education, advocacy and community awareness around substance use and addiction should be made to target and identify populations-at-risk with substance use and addiction in South Africa. Hence, to address this gap, it is therefore important that sensitization and reform health policies are developed and implemented to address health risks among these vulnerable substance users amidst the Covid-19 pandemic in South Africa